The influence of brand personality towards PETRONAS TV advertisement response: a study on PETRONAS Carigali Sdn Bhd - Sabah Operation staff / Sofia Kamin - Kamin, Sofia (2010)
This research has been conducted in order to determine what are the brand personalities that represent the PETRONAS TV advertisement and how it influence the response of its audience where this is a case study of PETRONAS CarigaliSdn. Bhd. Staff. The three main objectives of this research are: